A comparative study on various cell sources for constructing tissue-engineered meniscus - Zheng, Rui; Song, Daiying; Ding, Yangfan; Sun, Binbin; Lu, Changrui; Mo, Xiumei; Xu, Hui; Liu, Yu; Wu, Jinglei (Frontiers in Bioengineering and Biotechnology, 2023)
Injury to the meniscus is a common occurrence in the knee joint and its management remains a significant challenge in the clinic. Appropriate cell source is essential to cell-based tissue regeneration and cell therapy. Herein, three commonly used cell sources, namely bone marrow mesenchymal stem cell (BMSC), adipose-derived stem cell (ADSC), and articular chondrocyte, were comparatively evaluated to determine their potential for engineered meniscus tissue in the absence of growth factor stimulus. Cells were seeded on electrospun nanofiber yarn scaffolds that share similar aligned fibrous configurations with native meniscus tissue for constructing meniscus tissue in vitro. Our results show that cells proliferated robustly along nanofiber yarns to form organized cell-scaffold constructs, which recapitulate the typical circumferential fiber bundles of native meniscus. Chondrocytes exhibited different proliferative characteristics and formed engineered tissues with distinct biochemical and biomechanical properties compared to BMSC and ADSC. Chondrocytes maintained good chondrogenesis gene expression profiles and produced significantly increased chondrogenic matrix and form mature cartilage-like tissue as revealed by typical cartilage lacunae. In contrast, stem cells underwent predominately fibroblastic differentiation and generated greater collagen, which contributes to improved tensile strengths of cell-scaffold constructs in comparison to the chondrocyte. ADSC showed greater proliferative activity and increased collagen production than BMSC. These findings indicate that chondrocytes are superior to stem cells for constructing chondrogenic tissues while the latter is feasible to form fibroblastic tissue. Combination of chondrocytes and stem cells might be a possible solution to construct fibrocartilage tissue and meniscus repair and regeneration.